తెలుగు ఇంటెన్సివ్ కోర్సు - Parimi Ramanarasimham (Central Institute of Indian Languages, Mysore, 2006)
It's all about how to teach basic foundations of telugu to non-telugu speakers/readers
An Intensive Course in Telugu
Keywords: Telugu; Intensive Course; Telugu; English